2021
DOI: 10.1177/11786329211026035
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Mental Health Services among the Elderly in the Rural of Vietnam: A Cross Sectional Survey in 2019

Abstract: While the burden of neurological and mental disorders has been drastically increased in Vietnam, the current mental healthcare services do not meet the public demand. In order to determine perceived barriers to the use of mental health services, we conducted a cross-sectional study on 376 elderly people from a rural district in Hanoi, Vietnam. We found that depression may be an important indicator of the need for formal and informal community and home care mental health services. Barriers to mental healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 27 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…The issue of availability was discussed in two studies [ 20 , 36 ]. The studies indicated that availability of healthcare services in rural areas is still a significant issue.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The issue of availability was discussed in two studies [ 20 , 36 ]. The studies indicated that availability of healthcare services in rural areas is still a significant issue.…”
Section: Resultsmentioning
confidence: 99%
“…The studies indicated that availability of healthcare services in rural areas is still a significant issue. The disparity in the availability of mental health services in the rural areas of Vietnam was reported as a barrier [ 36 ]. The availability issue was further discussed in terms of the limited number of health care professionals in rural areas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations